LEGAL JUSTICE FOR LOW-INCOME COMMUNITIES IN BALANCED RESIDENTIAL DEVELOPMENT: LEGAL JUSTICE FOR LOW-INCOME COMMUNITIES IN BALANCED RESIDENTIAL DEVELOPMENT - Asnawi, Asnawi; Prasetyo, Dedy Ardian; Salee, Achara (Yayasan Pusat Cendekiawan Intelektual Nusantara, 2024)
This research investigates legal protection for low-income communities in the context of balanced residential development in Indonesia. The study aims to analyze the policies and regulations surrounding balanced housing development while identifying solutions to promote social justice for low-income people (MBR). Grounded in Law No. 1 of 2011 on Housing and Settlement Areas, which mandates the government to address housing needs for MBR, the research reveals various implementation challenges. Utilizing a normative juridical approach, the analysis employs legal protection theory, development law theory, and human rights theory as frameworks. Findings indicate significant obstacles, including limited land availability and rising land prices, which hinder low-income individuals' access to decent housing. The research underscores the necessity for stricter legal protections and adaptable policy measures to achieve the objectives of balanced housing development effectively.